2019
DOI: 10.1161/circinterventions.118.007349
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Leaflet Thrombosis After Transcatheter Aortic Valve Replacement

Abstract: Background: The occurrence and clinical impact of untreated subclinical leaflet thrombosis beyond 1 year after transcatheter aortic valve replacement still remain unclear. Methods and Results: In a multicenter transcatheter aortic valve replacement registry, we analyzed data from 485 patients who underwent 4-dimensional multidetector computed tomography posttranscatheter aortic valve replacement performed to survey hypoattenuated leaflet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 22 publications
3
69
1
1
Order By: Relevance
“…However, we consistently observe smaller volume metric PVLs associate with higher magnitude RFVs and conversely; larger PVLs result in lower RFVs and shear forces. This is consistent with recently reported clinical experience where independent predictors of late leaflet thrombosis, up to 3 years post implant, were male sex and PVL less than mild [17]. Perhaps the most consequential outcome of our recent valve research is the use of data visualization, in the form of an exploratory graphic technique, to compare and screen valves, for inferred thrombotic potential, with well established clinical controls.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, we consistently observe smaller volume metric PVLs associate with higher magnitude RFVs and conversely; larger PVLs result in lower RFVs and shear forces. This is consistent with recently reported clinical experience where independent predictors of late leaflet thrombosis, up to 3 years post implant, were male sex and PVL less than mild [17]. Perhaps the most consequential outcome of our recent valve research is the use of data visualization, in the form of an exploratory graphic technique, to compare and screen valves, for inferred thrombotic potential, with well established clinical controls.…”
Section: Discussionsupporting
confidence: 88%
“…At near valve closure, flow dynamics can be considered analogous to transient valve stenosis, whereby regurgitation is increasingly constrained until complete, motionless, closed-valve conditions occur. During brief crucial moments preceding valve closure, localized prothrombotic microenvironments may be relevant to generation of high velocity leakage jets, flow unsteadiness, valve flutter, cyclic variability of PDVA, turbulence, and excessive shear forces that may induce blood element damage [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. These influences may impact multiple valve types for:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But it seems influent little on the result because previous studies find an impact of new‐onset but not pre‐existing AF on the early stroke in TAVR . And the incidence of stroke are still higher in MDCT‐defined LT in the included studies where rates of AF are equal in the LT and non‐LT group during 1‐year follow‐up. Large‐scale, standardized, MRI‐determined stroke studies, such as the TICTAVI (NCT02817789) and AUREA (NCT01642134) trials, are warranted to further elucidate whether LT detected by MDCT indicates the occurrence of stroke.…”
Section: Discussionmentioning
confidence: 88%
“…A previous meta‐analysis demonstrated that MDCT‐defined LT was associated with increased risk of cerebrovascular events and TIA, but not stroke, while another meta‐analysis showed that LT detected by echocardiography or MDCT was associated with increased risk of stroke . While we find similar results for TIA, we find that there is an increased risk of stroke in patients with MDCT‐defined LT. Rashid et al performed three studies that reported on the incidence of TIA, but only two studies are included in our study with moderate bias, because Yanagisawa et al reported on the same patient cohort in 2016 and did not report on the incidence of TIA in their most recent study. We believe that the heterogeneity of TIA in our study comes from the small sample size, in that the I 2 became 6% when we added the incidence of TIA reported by Yanagisawa et al in 2016 (Figure S10).…”
Section: Discussionmentioning
confidence: 99%